Water Footprint Analysis In Krueng Aceh Watershed, Aceh Province, Indonesia - Purwana Satriyo; Hidayat Pawitan; Yanuar J Purwanto; Yayat Hidayat (Graduate Program of Syiah Kuala University, 2017)
Water is one the most important natural resources to maintain human life and all other living things in the earth. Around 65% water were consumed for drinking purpose, while others were used for daily needs. The increasing amount of work on water use and scarcity in relation to consumption and trade has led to the emergence of the field of Water Footprint (WF). Climate change, rural development, world population growth and industrialization have placed considerable stress on the local availability of water resources. Thus, it is necessary to perform study in order to analyze water demands and supply for sustainable water availability. Recently, water footprint analysis has been widely draw attention to the scientists and engineers. The water footprint analysis is closely related with virtual water from which it is defined as total water volume used for consumption and trade. The main aim of this present study is to analyze and assess the total water requirement based on community water footprint in Krueng Aceh watershed area. The virtual water used in this study are dominant consumption food commodities. The result shows that water footprint per capita in Krueng Aceh watershed area was 674.52 m3/year. Water footprint for rural and urban population were 608.27 m3/year and 740.77 m3/year respectively. The WF of food consumption in urban area of Krueng Aceh watershed is 690.74 m3 / capita / year and 584.22 m3/capita/year or average 625.69 m3/capita/year, while for non-food, the WF per capita is 24.05 m3/year in rural or 32.46% of the total water footprint. Non-food consumption per capita in Krueng Aceh and in urban areas is 50.03 m3/year or 67.53%. The total water demand based on the water footprint is 378,906,655.05 m3 in 2015 which is consumed by most of residents in the Krueng Aceh watershed area. Furthermore, total WF in rural and urban area are 193,489,128.95 m3 and 185,417,526.10 m3 respectively.